Multiple gastrointestinal metastases of squamous-cell lung cancer: A case report. Issue 24 (June 2018) - Li, Xinyu; Li, Songhe; Ma, Zhiming; Zhao, Shutao; Wang, Xudong; Wen, Dacheng
Abstract: Rationale: Gastrointestinal multiple metastases of lung cancer are extremely rare. The majority of gastrointestinal metastasis cases are diagnosed at a late stage and the prognosis is extremely poor. This report describes the clinical characteristics and outcomes of a patient with gastrointestinal multiple metastases from squamous-cell lung cancer, with special emphasis on the diagnosis and treatment of metastatic lung cancer. Patient concerns: A 61-year-old man who presented with progressive abdominal distention was admitted to our hospital. Radiological examinations showed changes of post-primary pulmonary tuberculosis and mechanical obstruction of the small bowl. Histopathological findings of gastroscopic examination and biopsy specimens showed a diagnosis of squamous-cell carcinoma in the body of the stomach. Diagnoses: Postoperative histopathology confirmed a gastrointestinal multiple squamous-cell carcinoma in stomach and small bowl. Finally, squamous-cell lung cancer was confirmed by lung biopsy. Interventions: During his hospitalization urgent surgery was performed because of acute abdomen. The patient underwent a laparotomy with curative gastrectomy for gastric cancer and small bowel partial resection. The patient was recommended with combination chemotherapy of carboplatin and paclitaxel for 3 cycles. Outcomes: Six months later after operation, the patient succumbed to respiratory failure. Lessons: We searched the related literature of gastrointestinal metastases from lung cancer and the clinical presentation, site of metastasis, diagnosis, treatment, and survival time in these cases were reviewed. The present study may increase the awareness of early diagnosis and appropriate treatment of metastatic lung cancer of gastrointestinal tract.